Determinasi Kepemimpinan Pelayan Pada PT. Kreasi Indah Busana Semarang - Sukardi Sukardi (FEB UNTAG Semarang, 2019)
This study aims to determine the effect of each servant leadership variable, career development, organizational commitment, capabilities, and teamwork on employee performance at PT. Kreasi Indah Busana Semarang. The population in this study all employees of PT. Kreasi Indah Busana Semarang, amounting to 461 people, while the sample size used was 82 respondents. The sampling technique is done by random sampling, especially using simple random sampling. Data collection techniques using questionnaires, and data analysis used is multiple linear regression analysis. Based on the results of the linear regression equation shows that servant leadership, career development, organizational commitment has a positive effect on employee performance. The coefficient of determination results obtained a value of 0.798, meaning that the servant leadership variable, career development, and organizational commitment can explain variations in employee performance variables of 79.8%. Hypothesis test results using the statistical test t obtained that servant leadership has a positive and significant effect on employee performance. Career development has a positive and significant effect on employee performance. Organizational commitment has a positive and significant effect on employee performance. Capabilities have a positive and significant effect on employee performance. Teamwork has a positive and significant effect on employee performance.Keywords: Servant Leadership, Career Development, Organizational Commitment, Capabilities, Teamwork and Employee Performance